Cover crops affect pool specific soil organic carbon in cropland : A meta‐analysis - Fohrafellner, Julia; Keiblinger, Katharina M.; Zechmeister‐Boltenstern, Sophie; Murugan, Rajasekaran; Spiegel, Heide; Valkama, Elena (Wiley-Blackwell, 2024)
Cover crops (CC) offer numerous benefits to agroecosystems, particularly in the realm of soil organic carbon (SOC) accrual and loss mitigation. However, uncertainties persist regarding the extent to which CCs, in co-occurrence with environmental factors, influence SOC responses and associated C pools. We therefore performed a weighted meta-analysis on the effects of CCs on the mineral-associated organic carbon (MAOC), the particulate organic carbon (POC) and the microbial biomass carbon (MBC) pool compared to no CC cultivation in arable cropland. Our study summarized global research of comparable management, with a focus on climatic zones representative of Europe, such as arid, temperate and boreal climates. In this meta-analysis, we included 71 independent studies from 61 articles published between 1990 and June 2023 in several scientific and grey literature databases. Sensitivity analysis was conducted and did not identify any significant publication bias. The results revealed that CCs had an overall statistically significant positive effect on SOC pools, increasing MAOC by 4.8% (95% CI: 0.6%–9.4%, n = 16), POC by 23.2% (95% CI: 13.9%–34.4%, n = 39) and MBC by 20.2% (95% CI: 11.7%–30.7%, n = 30) in the top soil, compared to no CC cultivation. Thereby, CCs feed into the stable as well as the more labile C pools. The effect of CCs on MAOC was dependent on soil clay content and initial SOC concentration, whereas POC was influenced by moderators such as CC peak biomass and experiment duration. For MBC, for example, clay content, crop rotation duration and tillage depth were identified as important drivers. Based on our results on the effects of CCs on SOC pools and significant moderators, we identified several research needs. A pressing need for additional experiments exploring the effects of CCs on SOC pools was found, with a particular focus on MAOC and POC. Further, we emphasize the necessity for conducting European studies spanning the north–south gradient. In conclusion, our results show that CC cultivation is a key strategy to promote C accrual in different SOC pools. Additionally, this meta-analysis provides new insights into the state of knowledge regarding SOC pool changes influenced by CCs, offering quantitative summary results and shedding light on the sources of heterogeneity affecting these findings.
Keywords: effect size; EJPSOIL; MAOC; MBC; POC; review; SOC; synthesis